1991
DOI: 10.1111/j.1365-2958.1991.tb00816.x
|View full text |Cite
|
Sign up to set email alerts
|

The spoIIIA operon of Bacillus subtilis defines a new temporal class of mother‐cell‐specific sporulation genes under the control of the σE form of RNA polymerase

Abstract: We have cloned and characterized a 5 kbp region of the Bacillus subtilis chromosome and show that it contains the promoter-proximal part of the spoIIIA locus. The locus consists of a polycistronic operon containing at least three genes. We show that the operon is regulated at the transcriptional level, from a promoter that is first activated about 80 minutes after the induction of sporulation, immediately after septation. Expression of spoIIIA in different spo mutant backgrounds correlates with the ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
67
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 54 publications
5
67
0
Order By: Relevance
“…A third class includes 20 genes which are maximally induced around 210 min, and whose expression persists at later times in development. spoIID (Rong et al, 1986) and the SpoIIID-repressed spoIIIA operon (Illing & Errington, 1991) are both found in class 1. Expression of the spoIIIA operon occurs transiently, prior to the accumulation of SpoIIID to high cellular levels (Illing & Errington, 1991), which fits well with the overall pattern of class 1 genes, and suggests that other genes in this class may be subjected to repression.…”
Section: Differentiation Of the Compartment-specific Sporulation Regumentioning
confidence: 99%
See 3 more Smart Citations
“…A third class includes 20 genes which are maximally induced around 210 min, and whose expression persists at later times in development. spoIID (Rong et al, 1986) and the SpoIIID-repressed spoIIIA operon (Illing & Errington, 1991) are both found in class 1. Expression of the spoIIIA operon occurs transiently, prior to the accumulation of SpoIIID to high cellular levels (Illing & Errington, 1991), which fits well with the overall pattern of class 1 genes, and suggests that other genes in this class may be subjected to repression.…”
Section: Differentiation Of the Compartment-specific Sporulation Regumentioning
confidence: 99%
“…spoIID (Rong et al, 1986) and the SpoIIID-repressed spoIIIA operon (Illing & Errington, 1991) are both found in class 1. Expression of the spoIIIA operon occurs transiently, prior to the accumulation of SpoIIID to high cellular levels (Illing & Errington, 1991), which fits well with the overall pattern of class 1 genes, and suggests that other genes in this class may be subjected to repression. In contrast, the spoIIID gene itself and spoIVCB (encoding the N-terminal half of s K ), both of which are known to be SpoIIID dependent Sato et al, 1994;Stevens & Errington, 1990), are found in class 2.…”
Section: Differentiation Of the Compartment-specific Sporulation Regumentioning
confidence: 99%
See 2 more Smart Citations
“…G accumulates in spoIIIA or spoIIIJ mutant cells but is unable to activate transcription from its target promoters (19,41). The spoIIIA operon encodes several putative membrane proteins and is expressed in the mother cell under the direction of E (15). The spoIIIJ gene is expressed during vegetative growth and encodes a membrane protein translocase of the YidC/Oxap1 family (6,27,48).…”
mentioning
confidence: 99%